Culture, Emotions, and Meaningful Learning in Physical Education - Mujica-Johnson, Felipe Nicolás (2021)
In the last decades, an affective shift has been developing in the theory and practice of pedagogical environments, which has caused emotions to be of greater importance in school learning. In this educational context, this essay has been elaborated with the objective of describing the relationship of cultural meanings with meaningful learning in the Physical Education subject based on an emotional perspective. The analyzes were mainly focused on the meanings associated with gender, socioeconomic status, and contact as cultural manifestations. Different studies are described that explain the influence of these aspects on the emotions of students during their motor learning. These meanings can alter the emotional disposition of students when learning new motor behaviors, so significant motor learning would also be affected. However, according to this theory, poor emotional disposition would not prevent developing new motor behaviors. Still, it would be important for teachers to have a good understanding of the motor capabilities of each student to optimize the process and not influence their subjective well-being negatively. It is concluded that in the face of cultural meanings that promote unpleasant emotions before some didactic content, it would be very useful to promote the acquisition of new meanings that have a contrary orientation to improve the emotional disposition of students.